Electrochemical impedance spectroscopy applied to microbial fuel cells: A review - Wang, Hui; Long, Xizi; Sun, Yingying; Wang, Dongqi; Wang, Zhe; Meng, Haiyu; Jiang, Chunbo; Dong, Wen; Lu, Nan (Frontiers in Microbiology, 2022)
Electrochemical impedance spectroscopy (EIS) is an efficient and non-destructive test for analyzing the bioelectrochemical processes of microbial fuel cells (MFCs). The key factors limiting the output performance of an MFC can be identified by quantifying the contribution of its various internal parts to the total impedance. However, little attention has been paid to the measurement conditions and diagrammatic processes of the EIS for MFC. This review, starting with the analysis of admittance of bioelectrode, introduces conditions for the EIS measurement and summarizes the representative equivalent circuits plots for MFC. Despite the impedance from electron transfer and diffusion process, the effect of unnoticeable capacitance obtained from the Nyquist plot on MFCs performance is evaluated. Furthermore, given that distribution of relaxation times (DRT) is an emerging method for deconvoluting EIS data in the field of fuel cell, the applying of DRT-analysis to MFC is reviewed here to getting insight into bioelectrode reactions and monitors the biofilm formation. Generally, EIS measurement is expected to optimize the construction and compositions of MFCs to overcome the low power generation.